SOSIALISASI PEMANFAATAN SAMPAH ORGANIK SISA RUMAH TANGGA MENJADI PUPUK ORGANIK CAIR BERBASIS ECOENZYM DAN BIOPORI DI KELURAHAN SEPAN - Anshory, Jamil; Shadrina, Alyani Nur; Lya, Putri; Pitriana, Pitriana; Lourenza, Sintikhe; Arso, Ali Dwi; Sumbafa, Shafa Rafa Tsamara; Hasugian, Tiurmaida; Lestari, Desy; Husein, Noval; Murtado, Dwi Ali; Gasama, Muhammad Garda (Madiun Spoor : Jurnal Pengabdian Masyarakat, 2025)
Kelurahan Sepan is one of the villages located in the Penajam District, Penajam Paser Utara Regency. One of the issues in Sepan Village is the lack of infrastructure, which impacts the mobility and daily life of the community. A specific problem is the absence of a waste disposal site (TPS), leading residents to dispose of waste carelessly. This activity aims to reduce waste accumulation by utilizing organic household waste as raw material for making easy and appropriate fertilizers. The method used includes socialization and direct practice, where the socialization is divided into three materials: an explanation of the types of waste, the procedure for making eco-enzyme, and biopore. The outcome of this activity is the successful implementation of socialization and direct practice among the residents of Sepan Village. Some residents understood the materials presented and successfully applied eco-enzyme and biopore techniques in their environment after the activity was completed.